Charpy impact response of fibre-metal laminates based on woven kenaf/glass fibre reinforced polypropylene - Dhar Malingam, Sivakumar; Ng, Lin Feng; Subramaniam, Kathiravan; Pilvamangalam, Nisallini; Bapokutty, Omar; Ab Ghani, Ahmad Fuad (Praise Worthy Prize, 2020)
Fibre Metal Laminates (FMLs) possess several advantages over their constituents, such as metallic alloys and composite materials. FMLs offer high impact and fatigue resistance to the entire structure, providing structural integrity and safety, which is required in the transportation field. The objective of this study is to investigate the Charpy impact behaviour of FMLs with different kenaf (K)/glass (G) fibre configurations. Composite panels have been fabricated through the hot press moulding compression method. FML panels have been formed by bonding the metallic skin layers to the composite laminates. Charpy impact test has been conducted using 50J Charpy hammer following ASTM E-23 in edgewise and flatwise impact orientations. Results have demonstrated that hybrid FMLs with the placement of glass fibres in the outer layers of hybrid composites have shown the highest Charpy impact energy absorption for both impact orientations. The energy absorption for G/K2/G FMLs has been 3.5% and 0.9% higher than non-hybrid glass fibre reinforced FMLs in edgewise and flatwise impact orientations respectively. The non-hybrid kenaf fibre reinforced FMLs have given the lowest impact energy absorption regardless of impact orientations.